Effect of roflumilast on exacerbations in patients with severe chronic obstructive pulmonary disease uncontrolled by combination therapy (REACT): a multicentre randomised controlled trial. Issue 9971 (7th March 2015) - Martinez, Fernando J; Calverley, Peter M A; Goehring, Udo-Michael; Brose, Manja; Fabbri, Leonardo M; Rabe, Klaus F
Summary: Background: Roflumilast reduces exacerbations in patients with severe chronic obstructive pulmonary disease. Its effect in patients using fixed combinations of inhaled corticosteroids and longacting β2 agonists is unknown. We postulated that roflumilast would reduce exacerbations in patients with severe chronic obstructive pulmonary disease at risk for exacerbations, even in combination with inhaled corticosteroid and longacting β2 agonist treatment. Methods: For this 1-year double-blind, placebo-controlled, parallel group, multicentre, phase 3–4 trial, the Roflumilast and Exacerbations in patients receiving Appropriate Combination Therapy (REACT) study, we enrolled patients with severe chronic obstructive pulmonary disease from 203 centres (outpatient clinics, hospitals, specialised pulmonologists, and family doctors) in 21 countries. Eligible patients were 40 years of age or older with a smoking history of at least 20 pack-years and a diagnosis of chronic obstructive pulmonary disease with severe airflow limitation, symptoms of chronic bronchitis, and at least two exacerbations in the previous year. We used a computerised central randomisation system to randomly assign patients in a 1:1 ratio to the two treatment groups: roflumilast 500 μg or placebo given orally once daily together with a fixed inhaled corticosteroid and longacting β2 agonist combination. Background tiotropium treatment was allowed. All patients and investigators were masked to group assignment. The primary outcome was the rate of moderate to severe chronic obstructive pulmonary disease exacerbations per patient per year, analysed by intention to treat. This study is registered withClinicalTrials.gov, numberNCT01329029 . Findings: Between April 3, 2011, and May 27, 2014, we enrolled 1945 eligible participants and randomly assigned 973 to the roflumilast group and 972 to the placebo group. The rate of moderate-to-severe chronic obstructive pulmonary disease exacerbations was 13·2% lower in the roflumilast group than in the placebo group according to a Poisson regression analysis (roflumilast 0·805 vs placebo 0·927; rate ratio [RR] 0·868 [95% CI 0·753–1·002], p=0·0529), and 14·2% lower according to a predefined sensitivity analysis using negative binomial regression (0·823 vs 0·959; 0·858 [0·740–0·995], p=0·0424). Adverse events were reported by 648 (67%) of 968 patients receiving roflumilast and by 572 (59%) of 967 patients in the placebo group; adverse event-associated patient withdrawal from the study was also more common in the roflumilast group (104/968 [11%]) than in the placebo group (52/967 [5%]). The most frequently reported serious adverse events were chronic obstructive pulmonary disease exacerbations and pneumonia, and 17 (1·8%) deaths occurred in the roflumilast group compared with 18 (1·9%) in the placebo group. Interpretation: Our findings suggest that roflumilast reduces exacerbations and hospital admissions in patients with severe chronic obstructive pulmonary disease and chronic bronchitis who are at risk of frequent and severe exacerbations despite inhaled corticosteroid and longacting β2 agonist therapy, even in combination with tiotropium. Funding: Takeda.